Low level laser application reduces the effect of 5 fluorouracil/leucovorin combination on human breast cancer cells - Guler, Yilmaz; Suat Ovey, Ishak; Nemutlu Samur, Dilara; Karabulut, Bayhan (Annals of Medical Research, 2021)
None
Keywords: Breast cancer; 5-fluorouracil; leucovorin; low level laser; TRPA1